A New Twist to a Chronic HCV Infection: Occult Hepatitis C - Bashar M. Attar; David Van Thiel (Gastroenterology Research and Practice)
Background. The prevalence of occult hepatitis C infection (OCI) in the population of HCV-RNA negative but anti-HCV positive individuals is presently unknown. OCI may be responsible for clinically overt recurrent disease following an apparent sustained viral response (SVR) weeks to years later. Purpose. To review the available current literature regarding OCI, prevalence, pathogenic mechanisms, clinical characteristics, and future directions. Data Sources. Searching MEDLINE, article references, and national and international meeting abstracts for the diagnosis of OCI (1990–2014). Data Synthesis. The long-term followup of individuals with an OCI suggests that the infection can be transient with the loss of detectable HCV-RNA in PPBMCs after 12–18 months or alternatively exist intermittently and potentially long term. The ultimate outcome of HCV infection is decided by interplay between host immune responses, antiviral therapies, and the various well-identified viral evasion mechanisms as well as the presence of HCV infection within extrahepatic tissues. Conclusion. The currently widely held assumption of a HCV-cure in individuals having had “SVR” after 8–12 weeks of a course of DAA therapy as recently defined may not be entirely valid. Careful longitudinal followup utilizing highly sensitive assays and unique approaches to viral isolation are needed.